A note on impact of new economic reforms on the elasticity of substitution in Indian industries: alternative measures. (18th November 2009) - Singh, Bhupendra V.; Sharma, Akhilesh K.
The year 1991 is the year of U-turn for economic policies in India. The process of new economic reforms, started in full sway in this year, has affected significantly, more or less, every sector of the economy. The present paper tries to find out changing substitutability amidst capital and labour in Indian industries as whole over pre- and post-reform periods. For this, three alternative models of VES production function have been chosen for estimation. The impact of reforms is captured by using separate datasets for pre- and post-reform period and also by using dummies. The elasticity of substitution obtained for all three VES production functions, for each pre- and post-reform periods, gives the similar trends, though their magnitudes are different. The elasticity of substitution in post-reform period is although, more than that of pre-reform period, the trend is decreasing.